Philippines, Bukidnon Panel Survey, 2003-2004 - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
This data set contains the 2003 and 2004 rounds of the Bukidnon Panel Survey, a survey spanning 19 years. Bukidnon is a landlocked province in the Philippines comprising 20 municipalities and two cities, Malaybalay and Valencia, on the island of Mindanao. The first rounds, in 1984 and 1985, collected data on food and nonfood expenditures, agricultural production, income, asset ownership, credit use, anthropometry and morbidity, education, and 24-hour food consumption recall. These rounds are also available from IFPRI’s website at http://www.ifpri.org/data/philippines01.htm. The 2003 and 2004 rounds, covering the originally sampled households and the households of children of the original householders – both those that live locally and migrants. The data cover similar topics as did the 1984/5 survey. These data are part of a rare long-term panel study that follows the migrant children of the households originally surveyed. They include sample and attrition weights, consumption and income aggregates, spatial data, and a good mapping of the 2003/4 rounds onto the 1984/5 rounds.